Structural – semantic character of the Adjective in English - T. Ataxojayev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article deals with the structural and semantic characteristics of the Adjective in the English language, its linguistic presentation in the language, its morphological composition, its syntactic functions, types of adjectives from semantic point of view.